Innovation in the firms of the agricultura sector of Costa Rica - Orozco-Barrantes, Jeffry (2022)
This article analyzes the innovation processes in the agricultural sector, using comparisons with the manufacturing sector and the service sector, on relevant issues. The study problem was defined based on the following question: what are the main characteristics of the innovation processes in the agricultural sector of Costa Rica? The information comes from indicators generated in different innovation surveys in the country, with emphasis on the last one that was carried out in 2019. These surveys are drawn up from a simple random sampling methodology, which was carried out by the National Institute of Statistics and Censuses (INEC), based on the directory of establishments in the different sectors. One of the findings is that there are few companies in the sector with significant innovations, but in general, those that have promoted innovations achieve positive impacts in various aspects of performance. It is also concluded that although there are policies to promote innovation in the sector, the scope has been very limited, since a series of barriers persist limiting the processes to achieve innovation. Some of the barriers identified have to do with deficiencies in the financial sector, but others are related to limitations in the type of interactions with different actors in the system.